A systematic integration of empirical and computational studies to biophysically describe recombinant nicotinate mononucleotide adenylyltransferase (NaMNAT) from Klebsiella pneumoniaeand Enterococcus faeciumby - Jeje, Olamide Adetomi (My University, 2021)
Background: The continuous threat of drug-resistant Klebsiella pneumoniae and Enterococcus faecium justifies identifying novel targets and developing effective antibacterial agents against these multi-drug-resistant pathogens. Given the vital role of NAD+in bacteria survival, nicotinate mononucleotide adenylyltransferase (NaMNAT) represents an attractive target for the design of novel antibiotics. NaMNAT activity is conserved in almost all living things, and the respective enzymes exhibit various structural and catalytic properties that reflect their species and specificity. They employ divalent cations for co-substrate binding and catalysis as metal-activated enzymes and have shown preferences for different divalent cations. In this study, NaMNAT from K. pneumoniae (KpNaMNAT) and E. faecium (EfNaMNAT) were biophysically described and compared using a combination of experimental and computational approaches. Methods: Overexpression of the enzymes was achieved with pET vector in Escherichia coli and was purified using a one-step nickel ion-immobilised metal affinity chromatography (IMAC). The activity of the enzymes was assayed via a dual enzyme catalysed reaction involving alcohol dehydrogenase at varying pH in the absence and presence of divalent cations. Far-UV circular dichroism, extrinsic fluorescence spectroscopy, and analytical SE‐HPLC were employed to assay the secondary content, tertiary, and quaternary structures. The stability of the enzymes was analysed via SYPRO Orange-based thermal shift assay in the absence and presence of varying divalent cations and ATP. Homology modelling, molecular docking, and molecular dynamic simulation were employed to complement the empirical studies. Results: The pET vector expression system and IMAC purification were efficient at overexpressing soluble enzymes and purifying the enzymes to homogeneity. Activity studies revealed both proteins to exhibit different catalytic properties. KpNaMNAT utilised NMN as substrate while demonstrating broad pH optimum of 6.5–9.5 and preference for Mg2+. Whereas EfNaMNAT showed minimal activity with NMN and a preference for Zn2+. Structural analysis showed both enzymes to be predominately α-helical, with KpNaMNAT existing mainly as a monomer while EfNaMNAT exists as a homodimer. KpNaMNAT exhibits a more hydrophobic binding compare to EfNaMNAT; however, the binding of ligands to this pocket did not induce conformational change in KpNaMNAT compared to EfNaMNAT. Thermal stability assay confirmed EfNaMNAT to be more stable than KpNaMNAT, and this stability is enhanced upon ligand binding. However, ligand binding did not impact the stability of KpNaMNAT; nonetheless, Zn2+and Cu2+alter the conformation of KpNaMNAT. Induced-fit ligand docking indicated that ATP, NMN, and NAD+bind at the same site on KpNaMNAT, and a 100 ns simulation revealed the ligands to be stabilised by H-bonds, water-bridges, electrostatic, and van der Waals interactions. The binding of the ligands does not severely perturb the global structure of KpNaMNAT. Overall, ATP is the most dynamic of all the three ligands, and Mg2+influences its dynamism. Conclusion: The differences demonstrated in the structure and function of these two enzymes provide insights into the distinctive features of NaMNAT from Gram-negative K. pneumoniae and Gram-positive E. faecium and a basis for structure-function comparison between the two classes of bacteria. This study is beneficial for the novel application of these enzymes and as a molecular basis for further evaluation of the enzymes for the rational design of inhibitors with therapeutic potential
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, 2021